Upaya Perlindungan Hukum dalam Hak Pekerja Difabel dalam Bekerja Ditinjau dari Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas Jo Undang-Undang Nomor 13 Tahun 2003 Ketenagakerjaan : Penelitian - Hutagalung, Natasya Juni Anggi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This study discusses legal protection efforts for the rights of workers with disabilities in the workplace, viewed from Law No. 8 of 2016 concerning Persons with Disabilities in conjunction with Law No. 13 of 2003 concerning Manpower. Although regulations guarantee the right of persons with disabilities to obtain equal employment opportunities, in reality, they still face discrimination, accessibility barriers, and injustice in the world of work. This research employs a normative juridical method with a descriptive- analytical approach by examining statutory regulations and legal theories related to the protection of disabled workers. The findings indicate that the rights of disabled workers—such as the right to work without discrimination, the right to fair wages, proper workplace accommodations, and protection from unilateral termination are explicitly regulated. However, the implementation remains suboptimal due to weak supervision, lack of strict legal sanctions, and persistent social stigma against people with disabilities. Therefore, greater commitment from the state, government, and employers is needed to create an inclusive and equitable work environment, in order to realize equal opportunities for all citizens without exception